2022
DOI: 10.1039/d1lc00995h
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a deformation-free plastic spiral inertial microfluidic system for CHO cell clarification in biomanufacturing

Abstract: Inertial microfluidics has enabled many impactful high throughput applications. However, devices fabricated in soft elastomer (i.e., polydimethylsiloxane (PDMS)) suffer reliability issues due to significant deformation generated by the high pressure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…Then, the particle trajectory was obtained by minimizing the vertical stacking through the ImageJ software for 600 pictures, as shown in Figure 5. It is worth noting that the experimental results may often have a certain deviation from the original design [36]. Through experiments, it was verified that the optimal input flow rate of the multistage channel was adjusted to 1.3 mL/min.…”
Section: Resultsmentioning
confidence: 97%
“…Then, the particle trajectory was obtained by minimizing the vertical stacking through the ImageJ software for 600 pictures, as shown in Figure 5. It is worth noting that the experimental results may often have a certain deviation from the original design [36]. Through experiments, it was verified that the optimal input flow rate of the multistage channel was adjusted to 1.3 mL/min.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to high separation efficiency, high throughput is another key advantage of the MDDS separation technology for large sample volume processing, which can solve a critical limitation of other microfluidic sperm separation technologies in terms of their commercialization 9 , 13 , 21 , 22 . Here, we showed that 1 mL of semen could be processed within 8.5 min in the high-throughput fluidic platform, and further throughput increase can be easily achieved by multiplexing or stacking the devices 30 , 45 48 . The advantage of high throughput could enable its standardized usage in handling semen samples with large variations in their cell number and volume (for normozoospermic men, the sperm count is in the range of 15–250 × 10 6 cells/mL in 1.5–7.6 mL semen) 43 .…”
Section: Discussionmentioning
confidence: 94%
“…Check valves (80183 and 80184, QOSINA, USA) were used to regulate the flow direction in the recirculation operation; we used the check-valves for single use to prevent potential cross-contamination caused by an internal membrane inside the check-valves. Furthermore, to switch to a single-use disposable medical device, the PDMS MDDS device can be translated to its plastic equivalent that is mass-producible 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow rate could not be increased for the 3000-ppm PEO solution considering the flow resistance in the microchannel due to the deformation of the polydimethylsiloxane (PDMS) channel. Using a rigid, deformation-free plastic-based microfluidic device with leak-tight connections [ 33 ], the device throughput and concentration performance can be further enhanced, finally enabling the commercialization process.…”
Section: Resultsmentioning
confidence: 99%